2004
DOI: 10.1074/jbc.m400268200
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for Aspartate-cleaved Bid in Apoptosis Signaling by DNA-damaging Anti-cancer Regimens

Abstract: Lymphoid malignancies can escape from DNA-damaging anti-cancer drugs and ␥-radiation by blocking apoptosis-signaling pathways. How these regimens induce apoptosis is incompletely defined, especially in cells with nonfunctional p53. We report here that the BH3-only Bcl-2 family member Bid is required for mitochondrial permeabilization and apoptosis induction by etoposide and ␥-radiation in p53 mutant T leukemic cells. Bid is not transcriptionally up-regulated in response to these stimuli but is activated by cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 62 publications
0
42
1
Order By: Relevance
“…As mentioned previously, a separate study using Jurkat T cells suggested that tBid was required for apoptosis signaling during DNA damage-induced apoptosis (38). The authors also concluded that Bid cleavage occurred independently of caspase activity.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…As mentioned previously, a separate study using Jurkat T cells suggested that tBid was required for apoptosis signaling during DNA damage-induced apoptosis (38). The authors also concluded that Bid cleavage occurred independently of caspase activity.…”
Section: Resultsmentioning
confidence: 75%
“…Furthermore, a different study reported that tBid is important during DNA damage-induced apoptosis and that the cleavage of Bid to tBid in this context was not caspase-dependent. Instead, cleavage was suggested to occur by an unidentified aspartate protease (38). The same study concluded that the importance of tBid for genotoxic stress-induced apoptosis was that it functioned to promote MOMP upstream of caspase activation.…”
Section: Resultsmentioning
confidence: 92%
“…These cells have one wild-type and one mutant p53 allele and undergo DNA damage-induced apoptosis in a p53-independent manner (Werner et al, 2004;Wissink et al, 2006). J16 cells, stably overexpressing Bcl-2 (J16-Bcl-2) or the dnCaspase-9 active site mutant C287A (J16-dnC9), were generated by retroviral transduction (Werner et al, 2004).…”
Section: Cells and Stimulationmentioning
confidence: 99%
“…These cells have one wild-type and one mutant p53 allele and undergo DNA damage-induced apoptosis in a p53-independent manner (Werner et al, 2004;Wissink et al, 2006). J16 cells, stably overexpressing Bcl-2 (J16-Bcl-2) or the dnCaspase-9 active site mutant C287A (J16-dnC9), were generated by retroviral transduction (Werner et al, 2004). For apoptosis assays, J16 cells were stimulated with the indicated doses of death receptor ligand, etoposide or IR in Iscove's modified Dulbecco's medium with 5% fetal bovine serum and cultured for the indicated time periods at 371C, 5% CO 2 .…”
Section: Cells and Stimulationmentioning
confidence: 99%
“…40,48 Caspase 2 appeared to act either upstream or downstream of other caspases depending on the cell type and specific mode investigated. 40,[49][50][51][52][53] Interestingly, caspase 2-mediated cell death was even reported to occur in the absence of any detectable release of mitochondrial factors or even caspase 3 activation, which places caspase 2 independent of both the mitochondrial and death receptor pathways. 38 In cholangiocarcinoma cells, TMX was shown to activate caspase 2, whereas GMT had no effect (Figure 4a).…”
Section: Discussionmentioning
confidence: 99%